A thioethylalkylamido (TEA) thioester surrogate in the synthesis of a cyclic peptide via a tandem acyl shift - Taichi, Misako (2013)
The cyclic cystine-knot peptide, kalata B1, was synthesized by employing a novel Fmoc-compatible thioethylalkylamido (TEA) thioester surrogate via an N–S acyl shift followed by a thiol-thioester exchange reaction. TEA thioester surrogate is cost-effective, conveniently prepared in one-step with starting materials, readily available from commercial sources, and highly efficient in preparing peptide thioesters.